1997
DOI: 10.1523/jneurosci.17-11-04486.1997
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Somatosensory Information about Object Shape Control Manipulative Fingertip Forces

Abstract: We investigated the importance of visual versus somatosensory information for the adaptation of the fingertip forces to object shape when humans used the tips of the right index finger and thumb to lift a test object. The angle of the two flat grip surfaces in relation to the vertical plane was changed between trials from −40 to 30°. At 0° the two surfaces were parallel, and at positive and negative angles the object tapered upward and downward, respectively. Subjects automatically adapted the balance between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
151
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(163 citation statements)
references
References 53 publications
11
151
1
Order By: Relevance
“…Because a block design was used in the previous study, the present results obtained by an event-related design provide more compelling evidence that the supramarginal cortex is activated at the time point when the weight is actually changed. The updating of the sensorimotor memory representations of objects typically takes place on a single-trial basis during precision grip lifts (Gordon et al, 1993;Jenmalm and Johansson, 1997;Johansson and Westling, 1988). The activity in the supramarginal gyrus may signal the discrepancy between the predicted and actual sensory information (Blakemore and Sirigu, 2003), or the updating of the sensorimotor memories of the object's physical proprieties.…”
Section: Mismatch Between Predicted and Actual Weight And Updating Ofmentioning
confidence: 99%
“…Because a block design was used in the previous study, the present results obtained by an event-related design provide more compelling evidence that the supramarginal cortex is activated at the time point when the weight is actually changed. The updating of the sensorimotor memory representations of objects typically takes place on a single-trial basis during precision grip lifts (Gordon et al, 1993;Jenmalm and Johansson, 1997;Johansson and Westling, 1988). The activity in the supramarginal gyrus may signal the discrepancy between the predicted and actual sensory information (Blakemore and Sirigu, 2003), or the updating of the sensorimotor memories of the object's physical proprieties.…”
Section: Mismatch Between Predicted and Actual Weight And Updating Ofmentioning
confidence: 99%
“…Although learning of the predictive control of grip force has been examined, its generalization properties have previously not been examined. Previous studies of grip force learning have shown that grip force levels can be set without somatosensory feedback, anticipating the physical properties of the object, which include the object's weight, shape, and friction at its surface (Jenmalm and Johansson 1997;Westling 1984, 1988;Johansson and Cole 1994). Such object properties are learned through development, indicated by increasing ability to correctly parameterize grip force to the object being manipulated Forssberg et al 1991Forssberg et al , 1992Forssberg et al , 1995.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the load force is self-generated, for example, by pushing on the object using the other hand, then grip force anticipates the load force with near zero delay, suggesting a predictive process (Johansson and Cole 1992). Anticipatory grip force modulation has been shown to be scaled to object weight (Johansson and Westling 1988), texture (Johansson and Westling 1984), shape (Jenmalm and Johansson 1997), center of mass (Wing and Lederman 1998), and previous experience (Gordon et al 1993). Such prediction is not hard-wired but learned through development (Forssberg et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Without the sense of touch, subjects have severe difficulties maintaining a stable grasp or performing a complex action such as lightning matches [1,2]. Also in robot applications, lacking tactile feedback results in loosing an initially grasped object or failing to robustly carry out manipulation tasks [3].…”
Section: Introductionmentioning
confidence: 99%